Hearing loss screening methods at early ages - Mijares Nodarse, Eleina; Pérez Abalo, María Cecilia; Savio López, Guillermo (Auditio, 2021)
Hearing losses in childhood affect language development, as well as the emotional development of the child and its adaptation to the social and family environment. These adverse effects can be avoided if the diagnosis of hearing loss and the initiation of treatment and rehabilitation begin before 6 months of age. For the early detection of hearing disorders, various subjective (based on behavioral responses to sound stimuli) and objective (using various physiological responses) have been used. Currently the most effective and reliable methods are Otoacoustic Emissions (OAE) and Auditory Brainstem Evoked Potentials (ABR). Although these methods have been shown to be reliable, they still have some limitations that can be improved. Stable-state Auditory Evoked Potentials at Multiple Frequencies (ASSR to MF) have recently been proposed as a new alternative for the early screening of hearing impairment. This article analyzes the advantages and disadvantages of each of these methods, as well as the results that have been obtained when using them in the context of an auditory screening protocol. It is concluded that the ASSR to MF have a diagnostic efficiency equivalent to that of the ABR to click, which, together with its potential value in the identification of disorders with a predominance of medium and severe frequencies, suggests that this method, a once perfected, it could then be a valid alternative for auditory screening protocols.